The Impact of Sodium Lauryl Sulfate on Human Health and Environment - Ganesan, Subbulakshmi; Muniswamy, Jaikumar Rajavoor; Zoysa, Agampodi Sandali Inupama De; Bettaswamy, Priyanshu Gowda; Prasanna, Konkathi Lakshmi; Patil, Ambika (Asian Journal of Biological and Life Sciences)
There has been much discussion about the effects of Sodium Lauryl Sulphate (SLS), an anionic surfactant that is widely used in personal care and household cleaning products, on the environment and human health. This comprehensive review meticulously examines the effects of SLS on human health, dispelling prevalent misconceptions surrounding its ocular and dermal irritation potential, acute oral toxicity, oncogenicity, and alleged chronic health effects. Contrary to common beliefs, extensive scientific evidence consistently affirms the safety of SLS for use in consumer products when appropriately formulated and employed as intended. Additionally, the review delves into the environmental implications of SLS, focusing on its toxicity to aquatic ecosystems and biodegradability in natural environments. While SLS exhibits moderate toxicity to aquatic organisms in its raw form, its rapid biodegradation ensures minimal environmental impact, with decomposition by-products posing negligible harm to ecosystems. Overall, this review offers clarity on the genuine health implications of SLS, reinforcing its suitability for everyday use in household and personal care products while underscoring the importance of responsible formulation and usage practices.
Keywords: Environment; Human health; Sodium Lauryl Sulphate; Toxicity